Lithium carbonate-doped polyvinyl oxide aluminum high-temperature-resistant composite material and preparation method thereof

By introducing lithium carbonate-doped GlyPOSS grafted with α-alumina and modified with KH550 into HDPE, a multi-level rigid interface connection and ion association structure was constructed, which solved the problems of uneven dispersion and interface instability of HDPE/alumina composites under high temperature conditions. This achieved the material's creep resistance and dimensional stability at high temperatures, while maintaining good processability.

CN123042401APending Publication Date: 2026-11-06GUANGDONG BONNY NEW MATERIALS TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611415044.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-12
Publication Date
2026-11-06

AI Technical Summary

Technical Problem

Existing HDPE/alumina composite materials suffer from uneven dispersion of inorganic particles, unstable interfacial bonding, and poor polymer chain slippage and creep properties under high-temperature conditions, making it difficult to balance melt processability and high-temperature dimensional stability.

Method used

By employing lithium carbonate doping, GlyPOSS grafted with α-alumina was prepared, combined with KH550 silane coupling agent modification and a staged vacuum devouring process, to construct a multi-level rigid interface connection and ion association structure, ensuring the uniform dispersion and stable connection of inorganic particles in the polymer matrix.

Benefits of technology

It significantly improves the high-temperature creep resistance, thermal dimensional stability and thermal deformation properties of composite materials, while maintaining good melt processing fluidity and enhancing the overall performance stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure REF-OBJ-1789204296101-000001
    Figure REF-OBJ-1789204296101-000001
  • Figure REF-OBJ-1789204296101-000002
    Figure REF-OBJ-1789204296101-000002
  • Figure REF-OBJ-1789204296101-000003
    Figure REF-OBJ-1789204296101-000003
Patent Text Reader

Abstract

This invention discloses a lithium carbonate-doped polyethylene alumina high-temperature resistant composite material and its preparation method, belonging to the technical field of polyethylene composite materials. The method includes the following steps: GlyPOSS is reacted with aminated α-alumina, and the product is purified to obtain GlyPOSS-grafted α-alumina; EAA and antioxidant are mixed and plasticized, GlyPOSS-grafted α-alumina and triphenylphosphine are added and reacted, a lithium carbonate / EAA premix is ​​added and the reaction continues, followed by staged vacuum devolatilization, discharge, tableting, and pelletizing to obtain a reaction masterbatch, which is then melt-blended with HDPE, and after extrusion, water cooling, and pelletizing, the final product is obtained. This method solves the problem of improving the interfacial constraint stability between inorganic fillers and polymers while maintaining the melt processability and inorganic particle dispersion stability of the HDPE / Al2O3 composite system, thereby improving the dimensional stability and creep resistance of the composite material under high-temperature conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of polyethylene composite material technology, specifically relating to a lithium carbonate-doped polyethylene alumina high-temperature resistant composite material and its preparation method. Background Technology

[0002] High-density polyethylene (HDPE) has advantages such as low density, good chemical resistance, easy molding and processing, and low cost, and is widely used in structural components, insulation materials, and corrosion-resistant products. However, HDPE is a typical non-polar thermoplastic polymer, and its molecular chains mainly rely on van der Waals forces and chain segment entanglement to maintain structural stability. Under increased temperature and continuous load, the movement of polymer chain segments intensifies, making it prone to creep and dimensional deformation. Therefore, its high-temperature dimensional stability and long-term load-bearing capacity are somewhat limited.

[0003] Introducing inorganic fillers such as alumina into HDPE can improve the modulus and dimensional stability of the composite material by utilizing the high rigidity and thermal stability of inorganic particles. Among them, α-alumina has a large specific surface area and high surface energy, but its dry powder is prone to forming secondary agglomerates. When alumina is directly added to high-viscosity polyethylene melt, the limited shearing action during the melt processing is insufficient to fully break up the agglomerates, which easily leads to uneven dispersion of inorganic particles in the polymer matrix, forming local interfacial pores and stress concentrations, thereby affecting the consistency and stability of the composite material's properties.

[0004] On the other hand, alumina contains hydroxyl groups on its surface, while HDPE molecular chains are generally nonpolar, resulting in significant differences in their interfacial chemistry. Existing technologies typically improve the dispersion and interfacial bonding of alumina in polyolefins through wet dispersion, surface modification with silane coupling agents, or the introduction of compatible components containing polar groups. However, while relying solely on physical dispersion or low-molecular-weight dispersants can improve the stability of alumina slurries to some extent, some dispersants that are difficult to completely remove may cover the active hydroxyl groups on the alumina surface, affecting subsequent interfacial reactions. Furthermore, when using only ordinary silane treatment, the structure and reaction sites of the interfacial bonding layer are limited, making it difficult to simultaneously achieve stable dispersion of inorganic particles and subsequent polymer interfacial bonding.

[0005] For HDPE / alumina composites, simply increasing the inorganic filler content does not necessarily guarantee better high-temperature resistance. While increasing alumina content can enhance system rigidity, it also increases melt viscosity and the probability of interparticle contact and re-agglomeration. If there is a lack of stable interfacial bonding between inorganic particles and the polymer, polymer segments may still slip near the filler interface under sustained high-temperature loads. Interfacial debonding or localized stress concentration may also weaken the reinforcing effect of the inorganic filler. Therefore, simply increasing the inorganic filler content, enhancing surface polarity, or improving the crosslinking and ionic interaction strength of the system may lead to decreased melt flowability, dispersion difficulties, or poor processing stability.

[0006] Therefore, existing HDPE / alumina composites still need further solutions to the challenges of balancing inorganic particle dispersion, stable inorganic / polymer interface bonding, high-temperature confinement of polymer segments, and melt processability. How to improve the interfacial confinement stability between inorganic fillers and polymers while maintaining good melt processability and inorganic particle dispersion stability in the HDPE / Al2O3 composite system, thereby improving the dimensional stability and creep resistance of the composite under sustained high-temperature loading conditions, remains a technical problem to be solved in this field. Summary of the Invention

[0007] The purpose of this invention is to provide a lithium carbonate-doped polyethylene alumina high-temperature resistant composite material and its preparation method, which is used to improve the interfacial constraint stability between inorganic fillers and polymers while maintaining the melt processability and inorganic particle dispersion stability of the HDPE / Al2O3 composite system, thereby improving the dimensional stability and creep resistance of the composite material under high temperature conditions.

[0008] The objective of this invention can be achieved through the following technical solutions: A method for preparing a lithium carbonate-doped polyethylene alumina high-temperature resistant composite material includes the following steps: S1. GlyPOSS was reacted with aminated α-alumina, and the product was purified to obtain GlyPOSS-grafted α-alumina. S2. Take EAA and antioxidants, mix and plasticize them, add GlyPOSS grafted α-alumina and triphenylphosphine to react, add lithium carbonate / EAA premix to continue the reaction, perform staged vacuum devolatilization, discharge, tablet, and pellet to obtain reaction masterbatch; S3. Take the reaction masterbatch and HDPE for melt blending, and after extrusion, water cooling and pelletizing, the lithium carbonate-doped polyethylene alumina high temperature resistant composite material is obtained.

[0009] As a preferred embodiment of the present invention, in step S1, the mass ratio of GlyPOSS to aminated α-alumina is 2.1-5.2:100.

[0010] As a preferred embodiment of the present invention, in step S2, the mass ratio of EAA, antioxidant, GlyPOSS-grafted α-alumina, triphenylphosphine and lithium carbonate / EAA premix is ​​110-159:2-4:250-350:0.12-0.18:12-26.

[0011] As a preferred embodiment of the present invention, in step S3, the mass ratio of the reaction masterbatch to HDPE is 43-68:100.

[0012] As a preferred technical solution of the present invention, the preparation method of the aminated α-alumina is as follows: α-alumina is added to an ethanol-water mixture for pre-dispersion, the pH of the system is adjusted to acidic, and wet grinding is performed to obtain an α-alumina slurry; KH550 is added to an ethanol-water mixture, the pH of the system is adjusted to acidic, hydrolyzed, and then added to the α-alumina slurry, heated and refluxed, centrifuged, and the solid phase is collected and washed to obtain the final product.

[0013] As a preferred embodiment of the present invention, the wet grinding uses yttrium-stabilized zirconia beads as the grinding medium; the mass fraction of α-alumina in the obtained α-alumina slurry is 18-22 wt%; the mass ratio of yttrium-stabilized zirconia beads to α-alumina is 2.5-3.5:1; the wet grinding time is 45-90 min; and the amount of KH550 added is 1.5-2.5% of the mass of α-alumina.

[0014] As a preferred technical solution of the present invention, the preparation method of the lithium carbonate / EAA premix is ​​as follows: EAA is pulverized under liquid nitrogen cooling conditions and sieved to obtain EAA powder; lithium carbonate is mixed with the EAA powder to obtain the final product.

[0015] As a preferred embodiment of the present invention, the mass ratio of lithium carbonate to EAA powder is 2.04-5.19:10-21.

[0016] As a preferred technical solution of the present invention, the staged vacuum devolatilization refers to first adjusting the absolute pressure of the system to 70-80 kPa and maintaining it for 1-2 min, then reducing it to 45-55 kPa and maintaining it for 1-2 min, and finally reducing it to 20-40 kPa and maintaining it for 6-10 min.

[0017] Another objective of this invention is to provide a high-temperature resistant composite material of lithium carbonate-doped polyethylene alumina.

[0018] This method first prepares aminated α-alumina by dispersing it in an ethanol-water mixture. Under acidic conditions and with wet milling using yttrium-stabilized zirconia beads, the soft agglomeration structure of the alumina particles is effectively broken down, significantly increasing the specific surface area and surface hydroxyl activity, resulting in a uniformly dispersed α-alumina slurry with consistent particle size. Subsequently, the milled alumina particles are surface-functionalized using KH550 silane coupling agent. KH550 is dispersed in a low-water-alcohol system and hydrolyzed under acidic conditions, allowing silanol groups to be fully generated and uniformly grafted onto the alumina surface. Through condensation reactions, stable covalent bonds are formed, firmly constructing an amino-active functional layer on the alumina surface. Further, the aminated α-alumina is covalently grafted with GlyPOSS to construct a multi-level rigid interface structure on the alumina surface. The rigid silicon-oxygen framework of POSS significantly improves interfacial thermal stability and structural rigidity, while retaining some unreacted epoxy active groups, providing stable reaction sites for subsequent interfacial bonding with polymer carboxyl groups.

[0019] This invention employs a stepwise controllable reaction process to prepare a highly active reaction masterbatch. First, EAA and a compound antioxidant are melt-plasticized to ensure that the polymer matrix does not undergo thermo-oxidative degradation during high-temperature processing. Then, GlyPOSS-grafted α-alumina and triphenylphosphine catalyst are added. Under catalytic conditions, the residual epoxy groups on the POSS surface preferentially undergo ring-opening addition reactions with the carboxyl groups on the EAA molecular chain to generate stable β-hydroxy ester covalent bonds. This allows the inorganic rigid particles to form a continuous and dense covalent interface connection with the EAA polymer chain, effectively eliminating interfacial voids between the filler and the matrix, suppressing interfacial slippage and debonding during high-temperature stress processes, and significantly improving load transfer efficiency.

[0020] This invention employs a differentiated reaction sequence: first, interfacial covalent reaction, then, controlled ion association. After constructing the inorganic-polymer covalent interface, a lithium carbonate / EAA premix is ​​added to partially neutralize and modify the remaining carboxyl groups. This effectively avoids the competitive inhibition of premature carboxyl group lithiation on the epoxy ring-opening interface reaction, ensuring the integrity of the interfacial covalent connection. The lithium carbonate / EAA premix is ​​prepared by cryogenically pulverizing EAA with liquid nitrogen and sieving it to obtain fine EAA powder, which is then uniformly mixed with dry lithium carbonate powder. Using EAA powder as a dispersion carrier improves the problems of easy agglomeration and uneven local neutralization caused by direct lithium carbonate addition. This allows lithium carbonate to be uniformly dispersed in the melt and undergo a controlled neutralization reaction with the remaining carboxyl groups, forming uniformly distributed lithium carboxylic acid ion association points between polymer chains. This ion association structure effectively restrains the relaxation movement of polyethylene and EAA molecular chains under high-temperature conditions, significantly improving the material's high-temperature creep resistance and creep recovery performance.

[0021] After the masterbatch reaction is completed, a graded gradient vacuum devolatilization process is used to remove carbon dioxide, moisture, and trace volatile impurities generated during the reaction step by step. This effectively avoids instantaneous foaming of the melt, material entrainment, and the formation of internal micropore defects, significantly reducing the porosity of the masterbatch and improving the uniformity of the material structure and the stability of its performance. After devolatilization, the masterbatch is obtained through tableting, cooling, pelleting, and vacuum drying. Finally, the masterbatch is melt-blended and extruded with HDPE. Utilizing the good compatibility between EAA ethylene segments and HDPE, the modified alumina multi-level rigid interface and uniform ion-association structure are uniformly dispersed in the HDPE continuous matrix. Through the process design of masterbatch pre-reaction followed by matrix dilution, both the high conversion rate of the interface reaction and the controllability of the structure are ensured, while also taking into account the melt processing fluidity and molding processability of the composite material.

[0022] The beneficial effects of this invention are: This invention achieves efficient and uniform dispersion of α-alumina and amino functionalization modification through wet depolymerization, followed by sequential completion of POSS covalent grafting, phase interface covalent construction, EAA carboxyl group controllable ion association, staged vacuum devolatilization granulation, and melt blending with HDPE matrix, ultimately obtaining a high-temperature resistant polyethylene matrix composite material with excellent high-temperature creep resistance, thermal dimensional stability, heat deformation performance, and good processing fluidity. Detailed Implementation

[0023] Raw material pretreatment: Ethylene-acrylic acid copolymer (EAA, brand: Tianjin Xiens, product number: P-69358) and high-density polyethylene (HDPE, brand: Maclean, product number: H790495) were vacuum dried at 60±5℃ for 10h; antioxidant and triphenylphosphine were vacuum dried at 50±5℃ for 5h; lithium carbonate was vacuum dried at 120±5℃ for 5h, cooled and sealed for storage.

[0024] Example 1

[0025] α-Alumina was added to an ethanol-water mixture and stirred for 5 min to pre-disperse. The pH of the resulting dispersion was adjusted to 4.3 using a 1 mol / L acetic acid aqueous solution. Then, the mixture was transferred to a wet bead mill and wet-milled using yttrium-stabilized zirconia beads as the grinding medium to obtain an α-alumina slurry. The volume ratio of ethanol to water in the ethanol-water mixture was 9:1. The mass fraction of α-alumina in the obtained α-alumina slurry was 18 wt%. The mass ratio of yttrium-stabilized zirconia beads to α-alumina was 2.5:1. The wet milling time was 45 min.

[0026] KH550 was added to an ethanol-water mixture, and the pH of the system was adjusted to 4.3 using a 1 mol / L acetic acid aqueous solution. The mixture was stirred and hydrolyzed at 20°C for 30 min. The solution was then added dropwise to the resulting α-alumina slurry while stirring at 200 rpm. After the addition was complete, the temperature was raised to 58°C, and the mixture was stirred and reacted under reflux for 3 h. After the reaction was complete, the mixture was cooled, centrifuged, and the collected solid phase was washed three times with anhydrous ethanol and then twice with anhydrous tetrahydrofuran to obtain aminated α-alumina. The volume ratio of ethanol to water in the ethanol-water mixture was 9.5:0.5. The mass of the ethanol-water mixture was 8 times the mass of KH550. The amount of KH550 added was 1.5% of the mass of α-alumina.

[0027] Under nitrogen protection, γ-glycidyl etheroxysilyl sesquioxane (GlyPOSS) (brand: Aladdin Biochemical, product number: G140436) was dissolved in tetrahydrofuran to obtain an 8 wt% GlyPOSS solution. The obtained aminated α-alumina was adjusted to a 12 wt% aminated α-alumina slurry using tetrahydrofuran. Under stirring conditions of 20°C and 200 rpm, the obtained GlyPOSS solution was added dropwise to the aminated α-alumina slurry. The addition was completed. The temperature was then raised to 58℃, and the reaction was carried out for 4 hours under nitrogen protection and reflux. After the reaction was completed, the mixture was cooled, centrifuged, and the collected solid phase was washed three times with tetrahydrofuran, then replaced twice with tert-butanol. The resulting solid phase was then adjusted to a slurry with a solid content of 6 wt% using tert-butanol. The slurry was pre-frozen at -20℃ for 6 hours and then freeze-dried under vacuum at an absolute pressure of 30 Pa for 12 hours to obtain GlyPOSS-grafted α-alumina. The mass ratio of GlyPOSS to aminated α-alumina was 2.1:100.

[0028] EAA was pulverized under liquid nitrogen cooling and passed through a 500μm sieve. After sieving, it was sealed and warmed to room temperature to obtain EAA powder. Lithium carbonate that had been vacuum dried at 120℃ for 4 hours was weighed and added to a dry mixing container with the EAA powder. The mixture was mixed at room temperature for 5 minutes to obtain a lithium carbonate / EAA premix. The mass ratio of lithium carbonate to EAA powder was 2.04:10. EAA, antioxidant 1010, and antioxidant 168 were added to a mixer and plasticized for 4 minutes under nitrogen protection, at 140℃ and 40 rpm. GlyPOSS-grafted α-alumina and triphenylphosphine were added, and the material temperature was adjusted to 156℃ and the rotation speed was adjusted to 60 rpm. The reaction was continued for 12 minutes, and the material temperature was adjusted to 160℃ while maintaining the rotation speed at 60 rpm. At 0 rpm, lithium carbonate / EAA premix was added, and the reaction continued for 8 min under normal pressure and nitrogen protection. Staged vacuum devolatilization was then performed at 160℃ and 60 rpm (first, the absolute pressure of the system was adjusted to 70 kPa and held for 2 min, then reduced to 45 kPa and held for 2 min, and finally reduced to 20 kPa and held for 10 min). After devolatilization, the material was discharged and pressed into a 2 mm thick sheet under nitrogen protection. After cooling to 40℃, it was granulated and vacuum dried at 55℃ for 6 h to obtain the reaction masterbatch. The mass ratio of EAA, antioxidant 1010, antioxidant 168, GlyPOSS-grafted α-alumina, triphenylphosphine, and lithium carbonate / EAA premix was 110:1:1:250:0.12:12.

[0029] The obtained reaction masterbatch was mixed with HDPE and fed into a co-rotating twin-screw extruder for melt blending. After extrusion, water cooling, and pelletizing, the lithium carbonate-doped polyethylene alumina high-temperature resistant composite material was obtained. The mass ratio of the reaction masterbatch to HDPE was 43:100. The twin-screw extruder had a screw diameter of 20 mm, a length-to-diameter ratio of 40:1, and temperature zones from the feed port to the die head of 150°C, 160°C, 170°C, 175°C, 175°C, and 170°C, respectively. The screw speed was 250 rpm, the absolute pressure at the vacuum port was 20 kPa, and the average residence time was 2 min.

[0030] Example 2

[0031] α-Alumina was added to an ethanol-water mixture and pre-dispersed by stirring for 10 min. The pH of the resulting dispersion system was adjusted to 4.5 using a 1 mol / L acetic acid aqueous solution. Then, it was transferred to a wet bead mill and wet-milled using yttrium-stabilized zirconia beads as the grinding medium to obtain an α-alumina slurry. The volume ratio of ethanol to water in the ethanol-water mixture was 9:1. The mass fraction of α-alumina in the obtained α-alumina slurry was 20 wt%. The mass ratio of yttrium-stabilized zirconia beads to α-alumina was 3.0:1. The wet milling time was 65 min.

[0032] KH550 was added to an ethanol-water mixture, and the pH of the system was adjusted to 4.5 using a 1 mol / L acetic acid aqueous solution. The mixture was stirred and hydrolyzed at 25°C for 35 min. The solution was then added dropwise to the resulting α-alumina slurry while stirring at 250 rpm. After the addition was complete, the temperature was raised to 60°C, and the reaction was carried out under reflux for 3.5 h. After the reaction was completed, the mixture was cooled, centrifuged, and the collected solid phase was washed three times with anhydrous ethanol and then twice with anhydrous tetrahydrofuran to obtain aminated α-alumina. The volume ratio of ethanol to water in the ethanol-water mixture was 9.5:0.5. The mass of the ethanol-water mixture was 10 times the mass of KH550. The amount of KH550 added was 2.0% of the mass of α-alumina.

[0033] Under nitrogen protection, γ-glycidyl etheroxysilyl sesquioxane (GlyPOSS) was dissolved in tetrahydrofuran to obtain a 10 wt% GlyPOSS solution. The resulting aminated α-alumina was adjusted to a 15 wt% aminated α-alumina slurry using tetrahydrofuran. The GlyPOSS solution was added dropwise to the aminated α-alumina slurry at 25°C and 250 rpm with stirring. After addition, the temperature was raised to 60°C, and the reaction was carried out under nitrogen protection and reflux for 4.5 h. After the reaction, the mixture was cooled, centrifuged, and the collected solid phase was washed three times with tetrahydrofuran, then replaced twice with tert-butanol. The resulting solid phase was then adjusted to a slurry with a solid content of 8 wt% using tert-butanol. The slurry was pre-frozen at -20°C for 8 h, and then freeze-dried under vacuum at 30 Pa for 18 h to obtain GlyPOSS-grafted α-alumina. The mass ratio of GlyPOSS to aminated α-alumina was 3.8:100.

[0034] EAA was pulverized under liquid nitrogen cooling and passed through a 500μm sieve. After sieving, it was sealed and warmed to room temperature to obtain EAA powder. Lithium carbonate that had been vacuum dried at 120℃ for 4 hours was weighed and added to a dry mixing container with the EAA powder. The mixture was mixed at room temperature for 5 minutes to obtain a lithium carbonate / EAA premix. The mass ratio of lithium carbonate to EAA powder was 3.8:16. EAA, antioxidant 1010, and antioxidant 168 were added to a mixer and plasticized for 3 minutes under nitrogen protection, 145℃, and 50 rpm. GlyPOSS-grafted α-alumina and triphenylphosphine were added, and the material temperature was adjusted to 158℃ and the rotation speed was adjusted to 70 rpm. The reaction was continued for 15 minutes, and the material temperature was adjusted to 163℃ while maintaining the rotation speed at 70 rpm. The lithium carbonate / EAA premix was added and reacted for 10 min under normal pressure and nitrogen protection. Then, staged vacuum devolatilization was performed at 163℃ and 70 rpm (first, the absolute pressure of the system was adjusted to 75 kPa and held for 1.5 min, then reduced to 50 kPa and held for 1.5 min, and finally reduced to 30 kPa and held for 8 min). After devolatilization, the material was discharged and pressed into 2.5 mm thick sheets under nitrogen protection. After cooling to 40℃, the sheets were granulated and vacuum dried at 60℃ for 8 h to obtain the reaction masterbatch. The mass ratio of EAA, antioxidant 1010, antioxidant 168, GlyPOSS-grafted α-alumina, triphenylphosphine, and lithium carbonate / EAA premix was 137:1.5:1.5:300:0.15:19.

[0035] The obtained reaction masterbatch was mixed with HDPE and fed into a co-rotating twin-screw extruder for melt blending. After extrusion, water cooling, and pelletizing, the lithium carbonate-doped polyethylene alumina high-temperature resistant composite material was obtained. The mass ratio of the reaction masterbatch to HDPE was 58:100. The twin-screw extruder had a screw diameter of 20 mm, a length-to-diameter ratio of 40:1, and temperature zones from the feed port to the die head of 150°C, 160°C, 170°C, 175°C, 175°C, and 170°C, respectively. The screw speed was 280 rpm, the absolute pressure at the vacuum port was 30 kPa, and the average residence time was 2.5 min.

[0036] Example 3

[0037] α-Alumina was added to an ethanol-water mixture and pre-dispersed by stirring for 15 min. The pH of the resulting dispersion system was adjusted to 4.7 using a 1 mol / L acetic acid aqueous solution. Then, it was transferred to a wet bead mill and wet-milled using yttrium-stabilized zirconia beads as the grinding medium to obtain an α-alumina slurry. The volume ratio of ethanol to water in the ethanol-water mixture was 9:1. The mass fraction of α-alumina in the obtained α-alumina slurry was 22 wt%. The mass ratio of yttrium-stabilized zirconia beads to α-alumina was 3.5:1. The wet milling time was 90 min.

[0038] KH550 was added to an ethanol-water mixture, and the pH of the system was adjusted to 4.7 using a 1 mol / L acetic acid aqueous solution. The mixture was stirred and hydrolyzed at 30°C for 40 min. The solution was then added dropwise to the resulting α-alumina slurry while stirring at 300 rpm. After the addition was complete, the temperature was raised to 62°C, and the mixture was stirred and reacted under reflux for 4 h. After the reaction was completed, the mixture was cooled, centrifuged, and the collected solid phase was washed three times with anhydrous ethanol and then twice with anhydrous tetrahydrofuran to obtain aminated α-alumina. The volume ratio of ethanol to water in the ethanol-water mixture was 9.5:0.5. The mass of the ethanol-water mixture was 12 times the mass of KH550. The amount of KH550 added was 2.5% of the mass of α-alumina.

[0039] Under nitrogen protection, γ-glycidyl etheroxysilyl sesquioxane (GlyPOSS) was dissolved in tetrahydrofuran to obtain a GlyPOSS solution with a mass fraction of 8-12 wt%. The obtained aminated α-alumina was adjusted to an aminated α-alumina slurry with a mass fraction of 18 wt% using tetrahydrofuran. The obtained GlyPOSS solution was added dropwise to the aminated α-alumina slurry under stirring at 30°C and 300 rpm. After the addition was complete, the temperature was raised to 62°C and the mixture was heated under nitrogen protection. The reaction was carried out under protective and reflux conditions for 5 hours. After the reaction, the mixture was cooled, centrifuged, and the collected solid phase was washed three times with tetrahydrofuran, then replaced twice with tert-butanol. The resulting solid phase was then adjusted to a slurry with a solid content of 10 wt% using tert-butanol. The slurry was pre-frozen at -20°C for 10 hours and then freeze-dried under vacuum at an absolute pressure of 30 Pa for 24 hours to obtain GlyPOSS-grafted α-alumina. The mass ratio of GlyPOSS to aminated α-alumina was 5.2:100.

[0040] EAA was pulverized under liquid nitrogen cooling and passed through a 500μm sieve. After sieving, it was sealed and warmed to room temperature to obtain EAA powder. Lithium carbonate that had been vacuum dried at 120℃ for 4 hours was weighed and added to a dry mixing container with the EAA powder. The mixture was mixed at room temperature for 5 minutes to obtain a lithium carbonate / EAA premix. The mass ratio of lithium carbonate to EAA powder was 5.19:21. EAA, antioxidant 1010, and antioxidant 168 were added to a mixer and plasticized for 2 minutes under nitrogen protection, 150℃, and 60 rpm. GlyPOSS-grafted α-alumina and triphenylphosphine were added, and the material temperature was adjusted to 160℃ and the rotation speed was adjusted to 80 rpm. The reaction was continued for 18 minutes, and the material temperature was adjusted to 165℃ while maintaining the rotation speed at 80 rpm. At rpm, lithium carbonate / EAA premix was added, and the reaction continued for 12 min under normal pressure and nitrogen protection. Staged vacuum devolatilization was then performed at 165℃ and 80 rpm (first, the absolute pressure of the system was adjusted to 80 kPa and held for 1 min, then reduced to 55 kPa and held for 1 min, and finally reduced to 40 kPa and held for 6 min). After devolatilization, the material was discharged and pressed into 3 mm thick sheets under nitrogen protection. After cooling to 40℃, the sheets were granulated and vacuum dried at 65℃ for 10 h to obtain the reaction masterbatch. The mass ratio of EAA, antioxidant 1010, antioxidant 168, GlyPOSS-grafted α-alumina, triphenylphosphine, and lithium carbonate / EAA premix was 159:2:2:350:0.18:26.

[0041] The obtained reaction masterbatch was mixed with HDPE and fed into a co-rotating twin-screw extruder for melt blending. After extrusion, water cooling, and pelletizing, the lithium carbonate-doped polyethylene alumina high-temperature resistant composite material was obtained. The mass ratio of the reaction masterbatch to HDPE was 68:100. The twin-screw extruder had a screw diameter of 20 mm, a length-to-diameter ratio of 40:1, and temperature zones from the feed port to the die head of 150°C, 160°C, 170°C, 175°C, 175°C, and 170°C, respectively. The screw speed was 300 rpm, the absolute pressure at the vacuum port was 40 kPa, and the average residence time was 3 min.

[0042] Comparative Example 1 The difference from Example 2 is that the wet bead milling step of α-alumina is omitted.

[0043] Specifically, α-alumina was added to an ethanol-water mixture and stirred for 10 minutes for pre-dispersion. The pH of the resulting dispersion system was adjusted to 4.5 using a 1 mol / L acetic acid aqueous solution. Wet bead milling was not performed. KH550 treatment, GlyPOSS grafting, reaction with EAA, partial neutralization of lithium carbonate, preparation of reaction masterbatch, and melt blending with HDPE were carried out directly according to the method described in Example 2. The amount of other raw materials and process parameters were the same as in Example 2.

[0044] Comparative Example 2 The difference from Example 2 is that the KH550 anchoring step is omitted.

[0045] The obtained α-alumina slurry was centrifuged and washed with anhydrous ethanol, then replaced with tetrahydrofuran, and subsequently reacted directly with GlyPOSS under the GlyPOSS treatment conditions of Example 2. After treatment, it was washed three times with tetrahydrofuran, and then replaced with tert-butanol and freeze-dried according to Example 2. The resulting treated α-alumina was then reacted and blended with EAA, triphenylphosphine, lithium carbonate, and HDPE according to the method described in Example 2, with all other conditions remaining unchanged.

[0046] Comparative Example 3 The difference from Example 2 is that GlyPOSS grafting was not performed after KH550 modification. Specifically, α-alumina was wet-milled and KH550 was surface-treated according to the method described in Example 2 to obtain aminated α-alumina. GlyPOSS was not added; the obtained aminated α-alumina was directly subjected to tert-butanol replacement and freeze-drying. Subsequently, aminated α-alumina was used to replace GlyPOSS grafting in Example 2, and EAA melt mixing, partial neutralization of lithium carbonate, and blending with HDPE were performed according to the method described in Example 2, with all other conditions remaining the same.

[0047] Comparative Example 4 The difference from Example 2 is that lithium carbonate is not added. Following the method described in Example 2, GlyPOSS-grafted α-alumina was reacted with EAA at 158°C and 70 rpm for 15 min under the action of triphenylphosphine; subsequently, 16 parts by mass of EAA powder, but without lithium carbonate, was added, and mixing continued for 10 min at 163°C, 70 rpm, and under atmospheric pressure and nitrogen protection. Then, according to Example 2, staged vacuum devolatilization, preparation of the reaction masterbatch, and melt blending with HDPE were performed.

[0048] Comparative Example 5 The difference from Example 2 is that the interfacial reaction between GlyPOSS-grafted α-alumina and EAA, and the neutralization of lithium carbonate, are no longer carried out in stages. EAA, antioxidant 1010, and antioxidant 168 were plasticized for 3 minutes under the conditions of Example 2. Then, GlyPOSS-grafted α-alumina, triphenylphosphine, and a lithium carbonate / EAA premix consisting of 3.8 parts by weight of lithium carbonate and 16 parts by weight of EAA powder were simultaneously added to a mixer. The mixture was first mixed at 158°C and 70 rpm for 15 minutes, then heated to 163°C and mixed for another 10 minutes. Subsequently, staged vacuum devolatilization, masterbatch preparation, and melt blending with HDPE were performed under the conditions described in Example 2. The remaining raw material composition, total mixing time, and subsequent processing conditions were the same as in Example 2.

[0049] Comparative Example 6 The difference from Example 2 lies in the altered order of the POSS / EAA interfacial reaction and the lithium carbonate neutralization reaction. After plasticizing EAA, antioxidant 1010, and antioxidant 168, a lithium carbonate / EAA premix consisting of 3.8 parts by weight of lithium carbonate and 16 parts by weight of EAA powder was first added. The mixture was reacted for 10 minutes at 163°C, 70 rpm, and under atmospheric nitrogen protection, allowing some of the carboxyl groups in the EAA to undergo lithiation. Subsequently, the material temperature was adjusted to 158°C, and GlyPOSS-grafted α-alumina and triphenylphosphine were added. The reaction was continued for 15 minutes at 70 rpm. Then, the process of staged vacuum devolatilization, masterbatch preparation, and melt blending with HDPE was performed according to Example 2. All other conditions remained the same as in Example 2.

[0050] Comparative Example 7 The difference from Example 2 is that HDPE is not added after the preparation of the reaction masterbatch, but before the reaction of POSS-grafted α-alumina and EAA. Specifically, the corresponding amounts of EAA, HDPE, antioxidant 1010, and antioxidant 168 from Example 2 are added to a mixer and melt-mixed at 145°C and 50 rpm. Then, the same amounts of GlyPOSS-grafted α-alumina and triphenylphosphine as in Example 2 are added, and the mixture is reacted at 158°C and 70 rpm for 15 min. Next, a lithium carbonate / EAA premix consisting of 3.8 parts by mass of lithium carbonate and 16 parts by mass of EAA powder is added, and the mixture is reacted at 163°C and 70 rpm for 10 min. The mixture is then subjected to staged vacuum devolatilization as in Example 2. The resulting material is then homogenized, extruded, and pelletized under the same twin-screw extrusion conditions as in Example 2. Finally, the total amounts of HDPE, EAA, α-alumina, GlyPOSS, lithium carbonate, and other additives are consistent with those in Example 2.

[0051] Comparative Example 8 The difference from Example 2 is that lithium hydroxide of equal mass is used instead of lithium carbonate in Example 2, and it is premixed with 16 parts by mass of EAA powder, while the other conditions are the same as in Example 2.

[0052] Comparative Example 9 The difference from Example 2 is that the lithium carbonate in Example 2 is replaced with an equal mass of sodium carbonate, and it is premixed with 16 parts by mass of EAA powder. The rest of the composition and preparation method are the same as in Example 2.

[0053] Performance testing The composite materials obtained in Examples 1-3 and Comparative Examples 1-9 were vacuum dried at 60°C for 4 hours. The dried composite materials were preheated at 175°C without pressure for 5 minutes, then held under pressure at 10 MPa for 5 minutes, and then cooled to 40°C under the pressure before demolding. Test specimens of corresponding specifications were prepared according to different test items.

[0054] I. 110℃ Constant Load Tensile Creep Performance Test The procedure was performed according to ISO 899-1:2017. Composite materials were prepared into test strips with dimensions of 80 mm × 10 mm × 2 mm. The specimens were pre-equilibrated in a constant temperature test chamber at 110 ± 1 °C for 20 min, and then a constant tensile stress of 0.20 MPa was applied. The gauge length at the instant of loading was defined as L0, and the length changes were recorded at 1, 5, 10, 20, 30, 45, and 60 mins.

[0055] The tensile creep strain over 60 minutes is calculated using the following formula:

[0056] After loading for 60 minutes, unload the load and leave it at 110℃ for another 30 minutes. Measure the remaining length L. r The residual strain is:

[0057] It can also calculate the creep recovery rate:

[0058] II. Dimensional Change Rate under No Load at 110℃ The procedure was performed according to ASTM D1042-26. The composite material was made into 100mm × 10mm × 2mm test strips. Two gauge lines with a spacing of 80.00mm were set in the middle of the specimen, and the initial gauge length L0 was measured. The specimen was placed flat on a low-friction, heat-resistant support plate without external load and placed in an oven at 110±1℃ for 2 hours. After removal, it was cooled in an environment at 23±2℃ for 1 hour, and the gauge length L1 was measured.

[0059] The linear dimensional change rate is: .

[0060] III. Melt Flow Rate Test Melt volumetric flow rate (MVR) testing was conducted according to ISO 1133-1:2022. Composite material particles obtained from Examples 1-3 and Comparative Examples 1-9 were directly tested after vacuum drying at 60°C for 4 hours. The barrel temperature of the melt flow rate tester was set to 190±0.5°C. After the temperature stabilized, composite material particles were added to the barrel and compacted. The piston was inserted, and the mixture was preheated at 190°C for 5 minutes. Subsequently, a nominal load of 2.16 kg was applied, causing the molten material to be extruded through a standard die. The displacement measurement method was used to record the piston's movement distance within a specified time. The instrument calculated the melt volumetric flow rate (MVR) based on the barrel cross-sectional area, piston movement distance, and corresponding time, with units of cm. 3 / 10min.

[0061] IV. Linear Expansion Coefficient Test The mean linear expansion coefficient of composite materials was determined by thermomechanical analysis (TMA) according to ISO 11359-2:2021. Samples measuring 5mm × 5mm × 2mm were cut from sheets prepared according to the unified molding method described above, with the upper and lower surfaces of the samples kept flat and parallel. Before testing, the initial dimension L0 of the sample along the test direction at room temperature was measured. The sample was placed on the TMA stage, with the expansion probe perpendicular to the sample surface. A constant small load was applied to maintain stable contact between the probe and the sample without causing significant compressive deformation. The same probe and load conditions were used for different samples. Nitrogen was used as a protective gas. Under a stable nitrogen atmosphere, the temperature was increased from 30℃ to 120℃ at a rate of 5℃ / min, and the change in the sample dimension along the thickness direction as a function of temperature was continuously recorded. The sample dimensions L0 at 80℃ and 110℃ were recorded as follows. 80 and L 110 The average linear expansion coefficient at 80-110℃ is calculated using the following formula:

[0062] In the formula, α is the average linear expansion coefficient at 80-110℃, and the unit is K. -1 L0 is the initial dimension of the sample along the test direction at the reference temperature; L 80 and L 110 These are the dimensions of the sample along the test direction at 80℃ and 110℃, respectively; (110-80) is the temperature difference within the test temperature range, i.e., 30K.

[0063] V. Heat distortion temperature test The measurements were performed according to ASTM D648-18. Strip specimens measuring 127 mm × 12.7 mm × 3.2 mm were individually molded from the composite materials obtained in Examples 1-3 and Comparative Examples 1-9. All specimens underwent the same molding and cooling conditions. The specimens were placed sideways between the two supports of the heat distortion temperature tester. A load was calculated and applied based on the actual width and thickness of the specimen, resulting in an initial bending stress of 0.455 MPa on the outer fiber layer. The loaded specimens were placed in a heat-conducting medium and held at the initial temperature for 5 minutes to allow the initial creep induced by the load to stabilize. The displacement measuring device was then zeroed. The temperature was uniformly increased at a rate of 2.0 °C / min, while the deflection at the midpoint of the specimen was continuously monitored. When the deflection of the specimen relative to the zero-adjustment position reached 0.25 mm, the temperature of the heat-conducting medium was recorded and taken as the heat distortion temperature of the specimen.

[0064] VI. Tensile property testing The test was conducted according to ASTM D638-22. Composite materials obtained in Examples 1-3 and Comparative Examples 1-9 were used to prepare Type I dumbbell-shaped specimens using the same molding process. The total specimen length was 165 mm, the width of the narrow parallel section was 13 mm, the gauge length was 50 mm, and the thickness was controlled at 3.2 ± 0.4 mm. Before testing, the specimens were conditioned for 48 hours at 23 ± 2 °C and 50 ± 5% relative humidity. Testing was performed using an electronic universal testing machine. The specimens were clamped longitudinally in the upper and lower fixtures, ensuring the longitudinal axis of the specimen was aligned with the tensile direction to avoid clamping misalignment. An extensometer was installed in the gauge length section of the specimen, with 50 mm as the initial gauge length.

[0065] Tension was performed at a test speed of 5 mm / min, and the load and elongation changes were continuously recorded until the specimen broke.

[0066] Tensile strength is calculated using the following formula:

[0067] In the formula, Tensile strength, unit: MPa; F max A0 represents the maximum load during the tensile process of the specimen, in N; A0 represents the initial cross-sectional area of ​​the narrow parallel section of the specimen, in mm. 2 ; Elongation at break is calculated using the following formula:

[0068] In the formula, L is the elongation at break; L0 is the initial gauge length, taken as 50 mm; L b This is the gauge length at which the specimen breaks.

[0069] The test results are shown in Table 1 below: Table 1 Results of various performance tests

[0070] As shown in Table 1, Examples 1-3 all exhibited good high-temperature dimensional stability and creep resistance. Compared with Example 2, Comparative Example 1, without alumina wet depolymerization, showed a significant increase in creep strain, residual strain, and average coefficient of linear expansion of the composite material, while the elongation at break decreased significantly. This indicates that alumina pre-depolymerization is beneficial for improving the dispersion state of inorganic particles and reducing interface defects caused by particle agglomeration. Comparative Example 2, without KH550 anchoring, and Comparative Example 3, without GlyPOSS grafting, showed a decrease in high-temperature creep resistance and thermal dimensional stability, indicating that the continuous interface structure constructed by KH550 and GlyPOSS is beneficial for enhancing the interfacial constraint between inorganic particles and the polymer. In Comparative Example 4, without partial lithium-ion neutralization, although the melt volumetric flow rate and elongation at break were high, the tensile creep strain at 110°C, residual strain, absolute value of linear dimensional change rate, and average coefficient of linear expansion were all significantly increased, while the heat distortion temperature decreased. This indicates that the ion association formed after partial lithium-ion neutralization of the remaining EAA carboxyl groups is beneficial in limiting the continuous slippage of polymer segments under high-temperature conditions. Comparative Example 5 involved simultaneous interfacial reaction and lithiation, Comparative Example 6 involved lithiation followed by the POSS / EAA interfacial reaction, and Comparative Example 7 involved adding HDPE before the formation of the reaction masterbatch. The tensile creep strain at 110°C, residual strain, and average coefficient of linear expansion of these three groups were all higher than those of Example 2, while the heat distortion temperature was lower than that of Example 2. This indicates that completing the interfacial reaction between the POSS residual epoxy and EAA carboxyl groups first, then partially lithiating the remaining carboxyl groups, and finally adding HDPE after the above reactions are beneficial in obtaining a more stable high-temperature interfacial constraint structure. When Comparative Example 8 used lithium hydroxide as the lithium source, some of its high-temperature stability indicators were slightly better than those of Example 2, but its melt volumetric flow rate and elongation at break were significantly reduced. Example 2 maintained similar high-temperature creep resistance while exhibiting significantly better melt processability and ductility, indicating that using lithium carbonate as the lithium source is more beneficial for balancing high-temperature dimensional stability, creep resistance, melt processability, and mechanical toughness. In Comparative Example 9, after replacing the lithium carbonate with sodium carbonate, high-temperature creep and thermal dimensional stability decreased, further demonstrating that the ion association formed by lithium ions has a positive effect on the high-temperature constraint of this system.

Claims

1. A method for preparing a high-temperature resistant composite material of lithium carbonate-doped polyethylene alumina, characterized in that, Includes the following steps: S1. GlyPOSS was reacted with aminated α-alumina, and the product was purified to obtain GlyPOSS-grafted α-alumina. S2. Take EAA and antioxidants, mix and plasticize them, add GlyPOSS grafted α-alumina and triphenylphosphine to react, add lithium carbonate / EAA premix to continue the reaction, perform staged vacuum devolatilization, discharge, tablet, and pellet to obtain reaction masterbatch; S3. Take the reaction masterbatch and HDPE for melt blending, and after extrusion, water cooling and pelletizing, the lithium carbonate-doped polyethylene alumina high temperature resistant composite material is obtained.

2. The method for preparing a high-temperature resistant composite material of lithium carbonate-doped polyethylene alumina according to claim 1, characterized in that, In step S1, the mass ratio of GlyPOSS to aminated α-alumina is 2.1-5.2:

100.

3. The method for preparing a high-temperature resistant composite material of lithium carbonate-doped polyethylene alumina according to claim 1, characterized in that, In step S2, the mass ratio of EAA, antioxidant, GlyPOSS-grafted α-alumina, triphenylphosphine, and lithium carbonate / EAA premix is ​​110-159:2-4:250-350:0.12-0.18:12-26.

4. The method for preparing a high-temperature resistant composite material of lithium carbonate-doped polyethylene alumina according to claim 1, characterized in that, In step S3, the mass ratio of the reaction masterbatch to HDPE is 43-68:

100.

5. The method for preparing a lithium carbonate-doped polyethylene alumina high-temperature resistant composite material according to claim 1, characterized in that, The preparation method of the aminated α-alumina is as follows: α-alumina is added to an ethanol-water mixture for pre-dispersion, the pH of the system is adjusted to acidic, and wet grinding is performed to obtain α-alumina slurry; KH550 is added to an ethanol-water mixture, the pH of the system is adjusted to acidic, hydrolyzed, and then added to the α-alumina slurry, heated and refluxed, centrifuged, and the solid phase is collected and washed to obtain the final product.

6. The method for preparing a high-temperature resistant composite material of lithium carbonate-doped polyethylene alumina according to claim 5, characterized in that, The wet grinding process uses yttrium-stabilized zirconia beads as the grinding medium; the mass fraction of α-alumina in the resulting α-alumina slurry is 18-22 wt%; the mass ratio of yttrium-stabilized zirconia beads to α-alumina is 2.5-3.5:1; the wet grinding time is 45-90 min; and the amount of KH550 added is 1.5-2.5% of the mass of α-alumina.

7. The method for preparing a high-temperature resistant composite material of lithium carbonate-doped polyethylene alumina according to claim 1, characterized in that, The preparation method of the lithium carbonate / EAA premix is ​​as follows: EAA is pulverized under liquid nitrogen cooling conditions and sieved to obtain EAA powder; lithium carbonate is mixed with the EAA powder to obtain the final product.

8. The method for preparing a high-temperature resistant composite material of lithium carbonate-doped polyethylene alumina according to claim 7, characterized in that, The mass ratio of lithium carbonate to EAA powder is 2.04-5.19:10-21.

9. The method for preparing a high-temperature resistant composite material of lithium carbonate-doped polyethylene alumina according to claim 1, characterized in that, The staged vacuum devolatilization refers to first adjusting the absolute pressure of the system to 70-80 kPa and maintaining it for 1-2 minutes, then reducing it to 45-55 kPa and maintaining it for 1-2 minutes, and finally reducing it to 20-40 kPa and maintaining it for 6-10 minutes.

10. A high-temperature resistant composite material of lithium carbonate-doped polyethylene alumina, characterized in that, The high-temperature resistant composite material of lithium carbonate doped polyethylene alumina as described in any one of claims 1-9 was prepared.